Restoration of the Scott and Shackleton huts on Ross Island, 1960–61 - Quartermain, L. B. (Polar Record, 1961)
New Zealanders interested in Antarctic exploration have for some years been concerned about the condition of the old huts in McMurdo Sound, built and occupied by the expeditions of the “heroic age”, and during the past two or three years sporadic attempts have been made to tidy up Shackleton's hut at Cape Royds and Scott's hut at Cape Evans. Working parties from H.M.N.Z.S. Endeavour and men from “Scott Base” have done urgent repair work and a certain amount of cleaning up, but it was evident that a more extensive project, properly organized and supervised, was necessary if the huts were to be made readily accessible to interested visitors and restored to a condition more in keeping with their historical interest.